Algerian Administration between citizen participation and the influence of its behavioural organization. - bouaici, heceme (Journal of Social Sciences and Humanities, 2021)
Today's administrative work primarily requires the effectiveness and development of the human element. On the one hand, and the development of his behaviour and performance on the other This requires many skills and gains. Perhaps the subject of organizational culture recently won the attention of many theorists of strategic management, organizational behaviour and human resources management, as well as organizations sociology, as it is one of the basic factors determining the success and superiority of business organizations Currently, the talk is not only about administrative reform, but rather about the structural reconstruction of public administration as well, it is a comprehensive process that includes the restructuring of all components of public administration within the framework of a new vision of public administration in national action and the strategic goals to be achieved. On the other hand, the administrative behaviour in Algeria and its relationship with citizens is manifested by the desire to clarify its public and private goals through its legal system and not to look at citizens as mere beneficiaries who are awaiting administration services. Therefore, the administrative law in general and the Algerian administrative law in particular is based on the norms of administrative organization and administrative activity, the latter which shows management behaviour in a number of legal acts and behaviours or in a set of negative administrative practices. Consequ ently human resources management in general plays an influential role in fulfilling the requirements Achieving institutional excellence, which has made it important and vital; The need to move towards implementing the institution’s distinguished management has increased in light of the many changes and challenges witnessed in the current era: the knowledge and information revolution, the digital divide, globalization and its various ramifications